2021
DOI: 10.3390/pharmaceutics13020131
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-Derived Outer Membrane Vesicles are Potent Adjuvants that Drive Humoral and Cellular Immune Responses

Abstract: Discovery and development of novel adjuvants that can improve existing or next generation vaccine platforms have received considerable interest in recent years. In particular, adjuvants that can elicit both humoral and cellular immune responses would be particularly advantageous because the majority of licensed vaccines are formulated with aluminum hydroxide (alum) which predominantly promotes antibodies. We previously demonstrated that bacterial-derived outer membrane vesicles (OMV) possess inherent adjuvanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Typhimurium adjuvanted with B. pseudomallei OMVs to determine if oral immunization could elicit protective mucosal immunity against Salmonella . The addition of the OMVs can mimic a live bacterium to stimulate the immune response [ 14 ]. Indeed, B. pseudomallei OMVs have recently been shown to behave like and elicit similar protection to a live-attenuated vaccine [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typhimurium adjuvanted with B. pseudomallei OMVs to determine if oral immunization could elicit protective mucosal immunity against Salmonella . The addition of the OMVs can mimic a live bacterium to stimulate the immune response [ 14 ]. Indeed, B. pseudomallei OMVs have recently been shown to behave like and elicit similar protection to a live-attenuated vaccine [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of OMVs to other mucosal surfaces would be beneficial in defining their adjuvant role and whether they are capable of inducing both humoral and cellular immunity at any site or if this phenomenon is gut specific. In this study, we used B. pseudomallei OMVs based on previous literature showing their safety and efficacy both as a vaccine and an adjuvant [ 13 , 14 , 37 ]. Overall, this study highlights the first time that B. pseudomallei OMVs have been employed to adjuvant an oral vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that OMV are able to drive DC maturation. Indeed, native OMV derived from the facultative-intracellular bacterium Burkholderia pseudomallei were shown to favor DC maturation and activation both in vitro and in vivo in a mouse model (57). Moreover, Schetters et al demonstrated that the LPS present on OMV was able to induce, through the myeloid differentiation primary response 88 (Myd88) adapter protein, maturation of human monocyte-derived DCs, murine bone marrow-derived DCs and CD11c+ splenic DCs (58).…”
Section: Gaps On Understanding the Basis Of Gmma Immunogenicity And Potential Challengesmentioning
confidence: 99%
“…It is known that OMV are able to drive DC maturation. Indeed, native OMV derived from the facultative-intracellular bacterium Burkholderia pseudomallei were shown to favor DC maturation and activation both in vitro and in vivo in a mouse model ( 57 ). Moreover, Schetters et al.…”
Section: Gaps On Understanding the Basis Of Gmma Immunogenicity And Potential Challengesmentioning
confidence: 99%